The Swedish Experiment - Bjørk, Anders Anker; Elvander, Nils; Jakobsson, Ulf; Henrekson, Magnus; Olson, Mancur; Persson, Mats; Petersson, Olof; Svensson, Lars G.; Sørensen, Peter Birch; Karpaty, Patrik (Journal of Economic Literature, 1997)
The deterioration of economic performance in Sweden from about 1970 was to some extent result of a number of exogenous shocks and unnecessary policy mistakes. It was, however, also related to basic changes in economic and social system in Sweden in late 1960s and early 1970, when government spending, taxes, and regulations started to expand dramatically. It is also argued in paper that problematic political, economic, and social mechanisms had become embedded in long-term dynamics of system itself. These various experiences are background for recent reforms and retreats of the Swedish experiment.